Comparison between the molecular diagnostic test and chest X-ray combined with multi-slice spiral CT in the diagnosis of lobar pneumonia - Zhu, Huiping; Dong, Jianjun; Xie, Xufeng; Wang, Lei (Cellular and Molecular Biology, 2021)
Lobar pneumonia is an inflammatory condition of the lung that mainly affects the lobes of the lungs and the alveoli, and it is usually caused by a bacterial infection. There are many ways to diagnosis this disease. But an early and accurate method for lobar pneumonia diagnosis has an important role in its treatment. Therefore, in this study, a comparison between the molecular diagnostic test and chest x-ray combined with multi-slice spiral CT was done to find out better diagnosis of lobar pneumonia. For this purpose, 122 individuals suspected of lobar pneumonia were studied by clinical examination, chest X-ray, and multi-slice spiral CT. For the molecular diagnosis test, the multiplex PCR was used for two main causes of the disease, Streptococcus pneumoniae and Klebsiella pneumoniae. Results showed that the specificity for Chest X-ray + Multi-slice Spiral CT had the highest amount (82.8%), but high sensitivity (100%) belonged to a molecular diagnostic test for both bacteria. On the other hand, the sensitivity and specificity of Streptococcus pneumoniae were better than Klebsiella pneumoniae and the possibility of error in Streptococcus pneumoniae was lower than Klebsiella pneumoniae. In general, although the Chest X-ray + Multi-slice Spiral CT method was better than the molecular diagnosis test, it could not identify the causative agent and did not show a difference between pathogens for better antibiotic treatment, and also the possibility of diagnosis is low at the beginning of the disease. Therefore, according to the results of the current study, the best way to diagnose lobar pneumonia is to use both methods, simultaneously.